2010
DOI: 10.1007/s00468-010-0472-3
|View full text |Cite
|
Sign up to set email alerts
|

Microclimatic conditions determined by stem density influence leaf anatomy and leaf physiology of beech (Fagus sylvatica L.) growing within stands that naturally regenerate from clear-cutting

Abstract: Beech forests naturally regenerating from clear-cutting can exhibit different microclimates depending on size of saplings and stem density. When beech trees are young and stem density is low, the level of radiation inside the ecosystem reaching the soil surface is high; consequently, air and soil temperatures rise and the soil water content may decrease. These microclimatic parameters presumably will affect the anatomy, photosynthesis, and carbon metabolism of beech leaves. We studied the morphology and physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 46 publications
(51 reference statements)
3
15
0
Order By: Relevance
“…These findings indicated that morphological features of foliage depended on the tree size (and/or on the bio-sociological position in the stand) that in general would relate to light conditions. Our knowledge is in accordance with results of Closa et al (2012), who studied a young beech stand whose shaded foliage had much higher values of SLA (between ca 250 to 470 cm 2 per gram of mass) than the foliage exposed to sunlight (150-180 cm 2 ·g -1 ). For instance Milla et al (2008) stated that large leaves tend to require higher biomass investment per unit leaf area than the small ones.…”
Section: Allometry and Growth Efficiency On A Tree Levelsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings indicated that morphological features of foliage depended on the tree size (and/or on the bio-sociological position in the stand) that in general would relate to light conditions. Our knowledge is in accordance with results of Closa et al (2012), who studied a young beech stand whose shaded foliage had much higher values of SLA (between ca 250 to 470 cm 2 per gram of mass) than the foliage exposed to sunlight (150-180 cm 2 ·g -1 ). For instance Milla et al (2008) stated that large leaves tend to require higher biomass investment per unit leaf area than the small ones.…”
Section: Allometry and Growth Efficiency On A Tree Levelsupporting
confidence: 92%
“…foliage area expressed per weight unit) according to light intensity (e.g. Barna 2004;Closa et al 2012). In scientific literature SLA is the most frequent indicator of foliage structure (Reich et al 1998).…”
mentioning
confidence: 99%
“…The poor functional and quantitative understanding of forest microclimate contrasts with its high ecological relevance for many forest ecosystem processes (Breshears et al 1997;Chen et al 1999;Scharenbroch & Bockheim 2007;Vanwalleghem & Meentemeyer 2009;Closa, Irigoyen & Goicoechea 2010). For survival and growth of young tree seedlings, for instance, favourable T, air humidity and soil moisture are crucial determinants, especially until the root system is sufficiently developed and other factors such as light conditions and nutrient availability become limiting (Aussenac 2000;Wicklein et al 2012;Lloret, Penuelas & Estiarte 2005).…”
Section: Introductionmentioning
confidence: 99%
“…All the leaf functional variables (LMA, mean leaf surface, percentage of N, d 13 C of total organic matter, and stomatal densities) studied were within the range reported for healthy beech trees in the literature (Aussenac and Ducrey 1977;Balsberg Påhlsson 1989;Keitel et al 2006;Wang et al 2008Wang et al , 2011Closa et al 2010;Bresson et al 2011). All these parameters were similar for healthy and declining trees.…”
Section: Discussionmentioning
confidence: 93%